Pengaruh Fraud Diamond Terhadap Kecurangan Laporan Keuangan Organisasi Dinyatakan dalam Pemantauan Khusus yang Terdaftar di BEI (Periode 2021-2023) - Ahmad Khutsil Atok; Bambang Minarso; Rento Indah Hernawati; Agung Prajanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Financial statements are the basis for economic decisions for various stakeholders, but they are often manipulated through financial statement fraud, misleading statements, omission of material facts, or manipulation of accounting data. The Fraud Diamond Theory adds the capability element to the Fraud Triangle (pressure, opportunity, rationalization), emphasizing that fraud occurs only if the perpetrator also has the technical ability and position to carry it out. This study explores the influence of four factors: financial targets (ROA), ineffective monitoring (BDOUT), audit opinion, and change in directors on fraud, as measured by the F-Score. This study will use a quantitative approach, focusing on industrial sector organizations classified as special monitoring on the IDX for the 2021-2023 period. Using a purposive sampling method, a total of 36 data sets were collected for this study. The purpose of this analysis is to answer the study's hypotheses by applying structural equation modeling. After reviewing the research findings, the conclusion is that elements of company management and financial performance have varying impacts on the potential for financial statement manipulation, which is assessed using the F-Score model. Research data shows that financial targets (ROA), weak oversight (BDOUT), and audit opinions do not significantly impact the F-Score. Meanwhile, changes in the board of directors have a significant positive impact on the F-Score. This finding suggests that only director changes directly increase the risk of financial statement fraud, while performance targets, the oversight framework, and auditor assessments are inadequate indicators of fraud in the F-Score model.